1994
DOI: 10.1093/jnci/86.10.775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Networks on Cancer-Screening Behavior of Older Mexican-American Women

Abstract: Social networks appear to be an important determinant of cancer-screening behavior among low-income, older Mexican-American women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
2
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 0 publications
10
67
2
3
Order By: Relevance
“…Emotional support from close friends helped Greek women overcome personal fears or difficulties in having screening examinations (Suarez et al 1994). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional support from close friends helped Greek women overcome personal fears or difficulties in having screening examinations (Suarez et al 1994). …”
Section: Discussionmentioning
confidence: 99%
“…Women who did not have a communicational and confidential relationship with their family and friends were less likely to have mammograms (Suarez et al 1994;Tejeda et al 2009). Breast cancer experiences that arose from some interviewees' immediate networks created the emotion of fear towards breast cancer, which acted either as a motivation or as a barrier to mammography screening.…”
Section: Quality Versus Quantity Of Social Interactions and Theories/mentioning
confidence: 99%
“…Suarez et al [23] investigated the importance of social networks among various Latino groups, including Mexican-Americans, in influencing a woman to be screened for cervical cancer. Using the Social Network Index [24], it was found that, although "highly socially integrated" Latinas were more likely to have been recently screened for cancer, the effect of social integration was stronger for Pap smear utilization than for mammography utilization among Mexican women.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have assessed the importance of social support in promoting participation in cancer screening (Suarez et al, 1994;Suarez et al, 2000;Kinney et al, 2005), few studies have examined the relationship between social support and stages of adoption of cancer screening. Identifying differences in the specific aspects of social support associated with these stages of adoption may provide new insights that will help healthcare professionals design future interventions tailored to the specific needs and characteristics of the target screening population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining the effect of social networks on cancer screening behavior in general have generated mixed results, with some studies identifying a positive effect (Kang and Bloom, 1993;Kang et al, 1994;Suarez et al, 1994;Kinney et al, 2005), others and others observing no effect. The current study showed that respondents with a larger social network were more likely to be in the contemplation/action/maintenance, and the :http://dx.doi.org/10.7314/APJCP.2013.14.10.6095 Social Network and Gastric Cancer Screening Behavior in Koreans relapse risk/relapse stages versus the precontemplation stage.…”
Section: Discussionmentioning
confidence: 99%